Training of Cash Waqf Management on Da'i and Mubaligh - Achmad Soediro; Media Kusumawardani; Muhammad Farhan; Fardinant Adhitama; Hasni Yusrianti; Patmawati Patmawati; Anton Indra Budiman (Sricommerce: Journal of Sriwijaya Community Services, 2022)
Community Service Implementation Activities with the theme "Socialization and Education of Cash and Productive Waqf on Da'i Mubaligh in South Sumatra" were carried out at the end of November 2021 through an online system and this service activity was responded well by the participants. This can be seen from the evaluation that is filled in through the google form. Good responses regarding service activities are broadly divided into at least two things: first, this activity is able to increase participants' knowledge and; both presenters mastered the material presented well. Some participants suggested doing similar activities on a regular basis with deepened material. Suggestions for the next activity is that this activity is carried out face-to-face so that this activity is more interactive between the presenters and participants. In addition to providing an interactive impact, face-to-face can also provide a good relationship between Sriwijaya University and the Regional Management of the Indonesian Dai Association of Palembang.